Предмет: Алгебра, автор: fdsfewnfdiosmcds

Помогите...............................................

Приложения:

Ответы

Автор ответа: Universalka
0

1)\frac{6^{-4} }{(6^{-\frac{3}{5}}*6^{\frac{1}{5}})^{5}}=\frac{6^{-4}}{(6^{-\frac{2}{5}})^{5}}=\frac{6^{-4} }{6^{-2}}=6^{-4-(-2)}=6^{-4+2}=6^{-2}=\frac{1}{6^{2}} =\frac{1}{36}\\\\\\2)\sqrt[3]{\sqrt{52} -5}*\sqrt[3]{\sqrt{52}+5} =\sqrt[3]{(\sqrt{52}-5)(\sqrt{52}+5)}=\sqrt[3]{(\sqrt{52})^{2}-5^{2}}=\sqrt[3]{52-25}=\sqrt[3]{27}=\sqrt[3]{3^{3}}=3

Похожие вопросы
Предмет: Музыка, автор: ЕВГЕНТУС228